(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Background: Accidental or unintentional poisoning in young children (under the age of 5 years) is a common health related problem all over the world. The data resources by the World Health Organization stated unintentional poisoning is the third leading cause of death caused by unintentional injuries. Thus, this study aimed to assess how the hospital outpatient visitors deal with home medication in Jazan region, Saudi Arabia and to explore the relationship between how they deal with the home medications and gender. Methods: A cross sectional study was conducted in Jazan. The study was conducted using an online self-administered questionnaire via Google Form. Results: About 404 participants were enrolled in the current study. Almost 203 (50.2%) were males. Most of them were in the age group of 26-35 years (35.9%), were bachelor’s degree holders (50.5%) and married (76%). Around 365 (90.3%) participants kept medicines at any location inside their home. Of them, 149 (36.9%) kept medicines in the cabinet or safe locker. Majority (70.3%) of the participants ensured that medicines were placed out of the reach of children. The most common types of medicines stored at home were analgesics (70%) followed by cough cold and congestion medicines (55.9%). The height at which medicines were stored was equal to the adult height as stated by 236 (58.4%) participants. About 58 (14.4%) participants had previously witnessed incidents where children accidentally put medicines in their mouths. Only 63 (15.6%) participants had previously attended awareness session about the safe storage of medicines at home, while 295 (73%) participants were willing to attend a training session about the safe storage of medicines at home. Further, females tended to ensure that medicines were placed out of the reach of children more than males (P value = 0.026). Conclusion: Good level of knowledge and awareness about safe storage of medicines at home was found. The most frequently reported storage sites for medicines were found to be fridge and bedrooms. Few knowledge gaps were noted regarding the correct procedures adopted in a confirmed or suspicious case of medicine ingestion by children.